PERAN WANITA DALAM PENDIDIKAN ANAK PERSPEKTIF ISLAM - Nurlina Nurlina (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper examines the role of women in the education of children in the Islamic perspective that the role of women against children is very large in the formation of future generations. Given the magnitude of opportunities and opportunities of women as a mother role in initiating the process of education of children from an early age. The potential and ability of Muslim women is very influential to shape the colors and patterns of future generations of Muslims. Therefore, as a woman is expected to have a love that manifestly manifests in the way of raising, hugging, meet needs and make friends with children. Therefore women should seek to be a smart woman as a provision to educate their children, because a smart mother will give birth to intelligent children. Creating a great generation there are points that need to be a record for a woman to be played to her child that is aqidah, morals and prayers. Then the intelligence, tenacity, and the mother's temperament is the dominant factor for the child's future. That is the word of the wise man of old, If there are men who become scholars, scholar, prominent figures or warrior heroes, See who their mother is. Because Mother has a big role in shaping one's character and knowledge. Therefore, the mother is the center of children's education.